ASSESSING THE PERFORMANCE OF COOPERATIVE BANKS IN THE PHILIPPINES: A DATA ENVELOPMENT ANALYSIS - Dante R. Garcia; Maria Luisa P. Mirasol (International Journal of Accounting, Finance and Business, 2020)
This paper assesses the performance of cooperative banks (CBs) in the Philippinesfor the period 2015-2018 by calculating their technical efficiencies. Slack-based dataenvelopment analysis (SBM-DEA) was applied in a dataset of 23 CBs provided by BangkoSentral ng Pilipinas. Adopting the intermediation approach, total deposits and fixed assetswere used as input variables and total loans and other earning assets were used as outputvariables. Results showed that three CBs were efficiently strong having operated at their mostproductive scale size (MPSS), seven CBs were efficiently weak, six were inefficient (withoutslacks), and seven were inefficient (with slacks). On the average, the overall technicalefficiency is 64.1% implying that CBs need to reduce their inputs by 35.9% while producing thesame amount of outputs. The sources of inefficiency were identified to be both from poormanagement of inputs and inappropriate scale of operations. The CBs should improvemanagement competencies and practice rightsizing to achieve optimal scale of operations.